The Impact of Global Crises on Employment and Talent Needs in the It Sector: A Time-Series Analysis of COVID-19 Disruptions and AI-Driven Adaptations - Medeková, Kristína; Mikulcová, Petra (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This paper looks at how the COVID-19 crisis has affected jobs in the Slovak IT sector between 2013 and 2023, focusing on trends, regional differences, and remaining vacancies. Using time series analysis and ARIMA modelling, it examines employment changes over time and predicts future developments. In addition, the study conducts a regional analysis to examine differences between Slovak regions and a job vacancy analysis to uncover the need for new talent. The results show that IT employment temporarily declined during the peak of the pandemic in 2020 but quickly bounced back, largely due to telework and digitization efforts. As for regional differences, while Bratislava and other large cities have more IT employment, smaller cities struggle more with employment shortfalls. Despite the sector's resilience, vacancies remain problematic, signaling a mismatch between demand and available talent. Forecasts suggest modest employment growth in the IT sector, but uncertainty in the economy may pose a risk. The study highlights the need for targeted policies to address labor shortages and improve skills, especially in smaller cities. By analyzing the impact of crises, vacancies, and future employment trends, this research offers valuable insights for policymakers and businesses aiming to strengthen the IT workforce in Slovakia.